Workshop Pembuatan Poster Melalui Aplikasi Canva Sebagai Media Pembelajaran Digital bagi Peserta Didik Sekolah Menengah - Panjaitan, Ruqiah Ganda Putri; Indrayani, Yuliati; Utomo, Kiki Prio; Hiendro, Ayong; Hendri, Muhammad Irfani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to optimize creative potential and improve students' skills in making posters using the Canva application as a digital learning medium in the classroom. The method for implementing this service used workshops and socialization with participants, namely grade 8 students at SMPN 3 Sungai Kakap, Kubu Raya Regency, West Kalimantan. The instrument used at the evaluation stage was an assessment sheet consisting of four criteria and analyzed descriptively. The result of this service activity was an increase in students' understanding and skills in operating the Canva application to create learning posters. This is proven by the poster design made by the students which is good and attractive.